2016
DOI: 10.12968/joan.2016.5.2.70
|View full text |Cite
|
Sign up to set email alerts
|

Polydioxanone thread lifting: considerations and patient expectations

Abstract: The thread lift is becoming an increasingly popular treatment within the field of aesthetic medicine. The procedure can be performed using polydioxanone (PDO) threads to lift, tighten and rejuvenate areas of sagging skin, and minimise fatty tissue. This allows for the non-surgical redefinition of facial contours and enhancement of skin integrity. Thread lifting with PDO can also provide certain aspects of the much sought after surgical facelift in a clinic setting. PDO threads aim to promote targeted lipolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…PDO threads have bioabsorption period of about 6 months. Thread lifting is reliant on two mechanisms: physical thread strength to lift and hold sagging tissues, and the biological processes to improve skin and soft tissue quality as a reaction to the threads [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PDO threads have bioabsorption period of about 6 months. Thread lifting is reliant on two mechanisms: physical thread strength to lift and hold sagging tissues, and the biological processes to improve skin and soft tissue quality as a reaction to the threads [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Histological studies have demonstrated the thicker dermal papillae following PDO thread insertion, suggesting interstitial growth of new collagen components (neocollagenesis). All of these changes aid in the reduction of tissue laxity and help to rejuvenate the structure and appearance of skin, enhancing the lift obtained up to the endpoint of treatment (about 1-year post treatment) [17].…”
Section: Discussionmentioning
confidence: 99%
“…When reduction in volume due to a double chin was desired, monofilament PDO threads were used in a crosshatch technique to aid in lipolysis, along with tightening the skin, thus attempting to restore the optimal cervicomental angle. [6] To improve sagging and severe wrinkling, more stretch in the horizontal plane was desired, and hence to redrape the skin, we used PDO bidirectional barbed or PLLA bidirectional cone threads.…”
mentioning
confidence: 99%